2015
DOI: 10.15344/2456-446x/2015/103
|View full text |Cite
|
Sign up to set email alerts
|

Education and Training Required for the Digital Radiography Environment: A Non-interventional Quantitative Survey Study of Radiologic Technologists

Abstract: The purpose of this research was to evaluate the knowledge components of CR, and confidence and attitudes in using the system in clinical practice using a non-interventional quantitative cross-sectional survey design. Using snowball sampling (non-probability sampling), an online survey questionnaire was administered to 103 diagnostic technologists who routinely perform CR imaging in hospitals in British Columbia (BC). The results of the survey study showed that the response rate was 69%, and that most of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…[1][2][3][4] Meanwhile, DR still presents well-known challenges such as dose creep, processing complexity, and significant vendor variations. In addition, multiple studies have revealed a deficiency and disparity in technologist education and training in DR. [5][6][7] Due to these reasons, it might be relatively easy to trouble shoot for individual image quality concerns, but can be very complex to learn the true practice acquisition and processing patterns, especially in a large practice with many radiographic systems, multiple vendors/models, and diverse clinical exams.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Meanwhile, DR still presents well-known challenges such as dose creep, processing complexity, and significant vendor variations. In addition, multiple studies have revealed a deficiency and disparity in technologist education and training in DR. [5][6][7] Due to these reasons, it might be relatively easy to trouble shoot for individual image quality concerns, but can be very complex to learn the true practice acquisition and processing patterns, especially in a large practice with many radiographic systems, multiple vendors/models, and diverse clinical exams.…”
Section: Introductionmentioning
confidence: 99%